Adrenal Venous Sampling Could Be Omitted before Surgery in Patients with Conn's Adenoma Confirmed by Computed Tomography and Higher Normal Aldosterone Concentration after Saline Infusion Test - Holaj, Robert; Waldauf, Petr; Wichterle, Dan; Kvasnička, Jan; Zelinka, Tomáš; Petrák, Ondřej; Krátká, Zuzana; Forejtová, Lubomíra; Kaván, Jan; Widimský, Jiří (Diagnostics, 2022)
PURPOSE: Adrenal venous sampling (AVS) performed to distinguish unilateral and bilateral primary aldosteronism (PA) is invasive and poorly standardized. This study aimed to identify non-invasive characteristics that can select the patients with unilateral PA who could bypass AVS before surgery. METHODS: A single-center study collected a total of 450 patients with PA. Development and validation cohorts included 242 and 208 patients. The AVS was successful in 150 and 138 patients from the cohorts, and the unilateral PA was found in 96 and 94 patients, respectively. Clinical factors independently associated with lateralized AVS in multivariable logistic regression were used to construct a unilateral PA prediction score (SCORE). RESULTS: The proposed SCORE was calculated as a sum of the prevalence of adrenal nodule on computed tomography (2 points) and plasma/serum aldosterone concentration ≥ 165 ng/L after the saline infusion test (SIT) (1 point). Importantly, the SCORE = 3 points identified 48% of unilateral PA patients with a specificity of 100% in the development cohort. The zero rate of false-positive classifications was preserved with the same cut-off value in the validation cohort. CONCLUSIONS: AVS could be omitted before surgery in patients with typical Conn ́s adenoma provided the aldosterone concentration ≥ 165 ng/L after the SIT.